COLOR COMBINATION IN INTERIOR AND EXTERIOR DECORATION: आंतरिक एवं बाह्य सज्जा में रंग संयोजन - Chauhan, Sadhana (International Journal of Research -GRANTHAALAYAH, 2014)
Color is an integral part of our life, as much as this colorful world of ours is beautiful, as much as it is a world of these colors. In childhood, we are taught only the names of three primary colors: yellow, blue and red, but the truth is, we cannot limit colors to any number. There is no count of colors, because there are innumerable colors in this world. The reason for this is that by combining any two colors, we can create a third color and by altering the amount of those two colors we can create many light and dark colors. In this way, we can create innumerable colors from different cohesion (Buipdanjapavade). Color is the peak of beauty, and beauty is directly related to the heart. These colors are used in different forms of art and are used in different forms of art on an ornamental, artistic and symbolic basis. Like "Baiga women tattoo on their body, which itself is a modified structure consisting of many signs". 2 It is mainly found in the use of green color, which does not just enhance the beauty of the body, but it has all kinds of colors in it. There is also a belief in Baigao that the ability to resist from enemies also increases, as they increase the power of hands and feet. Tattooing is considered to be the jewel of the tribals, especially women, in their body, embellishes a variety of shapes. These figures have their own religious, spiritual, cultural and social importance. रंग हमारे जीवन का एक अभिन्न हिस्सा है, जितनी खुबसुरत हमारी यह रंगीन दुनिया है, उतनी ही विलक्षण इन रंगो की दुनिया है। बचपन में हमे सिर्फ तीन प्राथमिक रंगो के नाम सिखाये जाते है:- पीला, नीला और लाल, परन्तु सच तो यह है कि, किसी संख्या में रंगो को सीमित नही कर सकते। रंगो की कोई गिनती नही होती, क्योंकि इस दुनिया में असंख्य रंग है। इसका कारण यह है कि किन्ही भी दो रंगो को मिलाकर हम एक तीसरे रंग का निर्माण कर सकते है और उन दो रंगो की मात्रा में फेरबदल करके हम अनेक हल्के और गहरे रंगो का निर्माण कर सकते है। इस तरह हम अलग अलग सामंजस्य (ब्वउइपदंजपवदे) से असंख्य रंगो का निर्माण कर सकते है। रंग सुन्दरता की चरम विघा है और सुन्दरता का सीधा संबंध हृदय से है। यही रंग कला के भिन्न भिन्न रूपो में प्रयुक्त किऐ जाते है और कला की विभिन्न विघाओ में अलंकारिक, कलात्मक व सांकेतिक आधार पर उपयोग में लाऐ जाते है। जैसे ‘‘ बैगा स्त्रीयाॅ अपने शरीर पर गोदना गुदवाती है, जो स्वयं कई चिन्हो से मिलकर बनी एक संश्रृष्ट संरचना होती है ’’ 2 इसमें मुख्यतः हरे रंग का प्रयोग पाया जाता है, जो महज शरीर का सौन्दर्य ही नही बढाते वरन् उसमें तमाम तरह की विपदाओ से प्रतिरोध करने की क्षमता को भी बढाते है, जैसे हाथो व पैरो की शक्ति को बढाते है, ऐसी बैगाओ में मान्यता है। गोदना आदिवासियों का आभूषण माना जाता है, विशेषकर महिलाऐ अपने शरीर में तरह तरह की आकृतियाॅ गुदवाती है। इन आकृतियों का अपना धार्मिक, आध्यात्मिक, सांस्कृतिक और सामाजिक महत्व होता है।